Magie: Rezeptions- und diskursgeschichtliche Analysen von der Antike bis zur Neuzeit - Otto, Bernd-Christian (De Gruyter, 2011)
This book (the author’s revised dissertation) analyzes the history of the concept of magic spanning about 2,500 years. Following an introduction discussing the problem of academic definitions of magic in general, the book presents the comprehensive history of the concept of magic for the first time, from its origins in antiquity to the 20th century. Polemic texts with an external perspective are included in equal measure along with authors that described and understood themselves as “magicians” in Western cultural history.<br